4D Printed Light‐Responsive Patterned Liquid Crystal Elastomer Actuators Using a Single Structural Color Ink. Issue 3 (17th October 2022) - Sol, Jeroen A. H. P.; Douma, Robin F.; Schenning, Albert P. H. J.; Debije, Michael G.
Abstract: Envisioning robotic devices with functionality resulting from processing rather than exclusively material composition, multimodal responsive devices produced from a single azobenzene‐functionalized cholesteric liquid crystal elastomer ink are demonstrated. The resulting device displays simultaneous structural color and actuation in response to both ultraviolet and blue light exposures. Through direct ink writing, a microextrusion‐based additive manufacturing technique, the liquid crystalline ink is deposited into different effective mesophases—planar and slanted cholesteric, and a uniaxial pseudo‐nematic state—by altering only two printing conditions: deposition speed and time before photopolymerization. Comparing the three different printed mesophases, marked differences in optical properties and actuation behaviors are found. Demonstrators based on bilayer architectures present concepts for interactive soft multiactuators deposited in a single printing step from a single ink. Abstract : Multimodal responsive devices with three effective mesophase alignments are produced from a single azobenzene‐functionalized, cholesteric liquid crystal elastomer ink using a single direct ink writing event. The resulting devices display simultaneous structural color and actuation in response to both ultraviolet and blue light exposures.